Design and implementation of a foot pressure measurement - Mohammed Ziad Abdullah Nayef; Nafea badea allawi Dawood; Abdullah Ali Khalaf Awad; Harith Muthanna Abdul Halim; Taif Muhanna Azeez Dawud (Genius Journals, 2024)
Foot plantar pressure is the pressure field that acts between the foot and the support surface during everyday locomotor activities. Information derived from such pressure measures is important in gait and posture research for diagnosing lower limb problems, footwear design, sport biomechanics, injury prevention and other applications. This work explain the way and the main component that used to design a system for measuring foot pressure. This system is characterized by simplicity and portability. So, it suitable for patient and economically viable in countries with people having low socioeconomic status.
Keywords: Foot pressure; locomotor activities; measuring